Model of protection of the marine site the state border - Zaharchuk, D. О. (Honor and Law, 2019)
The article is devoted to the development and implementation of a model for the protection of the maritime area of the state border. Operational and operational activities of the border detachment on land and the protection of the state border at sea are organized at the same time and in the same sequence, but in the maritime sector, the basic elements of the existing model of protection are complemented by additional elements. This is a system for monitoring the situation at the state border and a system for responding to detected violators of the state border.